2001
DOI: 10.1097/00000374-200105051-00037
|View full text |Cite
|
Sign up to set email alerts
|

Role of Estrogen in Alcohol Promotion of Breast Cancer and Prolactinomas

Abstract: This article represents the proceedings of a symposium at the 2000 ISBRA Meeting in Yokohama, Japan. The chair was Dipak K. Sarkar. The presentations were (1) Dual role of estrogen as hormone and carcinogen in mammary carcinogenesis, by Joachim G. Liehr; (2) Alcohol and breast cancer: Studies using animals, by Keith W. Singletary; and (3) Evaluation of the role of estrogen in mediation of ethanol effect on prolactinoma: Studies using animals, by Dipak K. Sarkar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…The interaction of chronic alcohol intake with estrogen has been recognized in prolactinomas; however, the potential mechanism has not been clearly defined (Sarkar et al 2001). The present results demonstrated that a very low concentration of ethanol (0.01%) stimulated ERα signaling but suppressed the actions of 17β-estradiol (E2) in the rat pituitary somatolactotrope GH4C1 (GH4) cell line.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The interaction of chronic alcohol intake with estrogen has been recognized in prolactinomas; however, the potential mechanism has not been clearly defined (Sarkar et al 2001). The present results demonstrated that a very low concentration of ethanol (0.01%) stimulated ERα signaling but suppressed the actions of 17β-estradiol (E2) in the rat pituitary somatolactotrope GH4C1 (GH4) cell line.…”
Section: Discussionmentioning
confidence: 55%
“…Conversely, alcohol is also positively associated with the occurrence of cancers of various organs, particularly in postmenopausal women (Lieber et al 1979;Blot 1992;Singletary and Gapstur 2001;Pöschl and Seitz 2004;Boffetta and Hashibe 2006;Seitz and Stickel 2007). Alcoholic men frequently exhibit evidence of feminization, as manifested in gynecomastia, spider angiomata, palmar erythema, and changes in body hair pattern (Sarkar et al 2001). The mechanisms underlying these diverse effects are thought to be mediated by estrogen, since alcohol has been found, although not invariably, to elevate plasma estrogen levels (Ginsburg 1999;Purohit 2000;Singletary and Gapstur 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Like estradiol, ethanol reduces the activity of the growth-inhibitory TGF-␤1 and stimulates the activity of TGF-␤3 in the pituitary gland. Hence, it is hypothesized that ethanol may promote prolactinomas by controlling the cell-regulatory processes in the lactotropes and/or by enhancing the action of estrogen on the lactotropes [125].…”
Section: Alcohol and Estrogen Statusmentioning
confidence: 99%
“…As little as 5-6 g of daily alcohol intake has been found to significantly increase the risk of developing breast cancer [5] and breast cancer recurrence [3,6]. Mechanisms responsible for the increased risk may be due to increased estrogen and androgen levels [7,8] or increased levels of plasma insulin-like growth factors produced by the liver following alcohol consumption [9]. In addition, alcohol-related breast cancer risk may be compounded for individuals who have other lifestyle risk factors, such as obesity [6].…”
Section: Introductionmentioning
confidence: 99%